2023
DOI: 10.1111/infa.12568
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of children's verbal input in a forager‐farmer population using long‐form audio recordings and diverse input definitions

Camila Scaff,
Marisa Casillas,
Jonathan Stieglitz
et al.

Abstract: There is little systematically collected quantitative empirical data on how much linguistic input children in small‐scale societies encounter, with some estimates suggesting low levels of directed speech. We report on an ecologically‐valid analysis of speech experienced over the course of a day by young children (N = 24, 6–58 months old, 33% female) in a forager‐horticulturalist population of lowland Bolivia. A permissive definition of input (i.e., including overlapping, background, and non‐linguistic vocaliza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Another limitation was the use of elicited phrases, and the focus on one specific syllable, /ki/, as context for the perception study. We also hope to utilise other extant corpora (such as the Bible, mentioned in the Introduction) to study this contrast in a wider variety of materials, including some from spontaneous conversations and extant child-centered corpora [16]. Our perceptual study is also affected by a relatively small sample size, although results are quite clear in that they suggest the contrast is easily recovered by listeners.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was the use of elicited phrases, and the focus on one specific syllable, /ki/, as context for the perception study. We also hope to utilise other extant corpora (such as the Bible, mentioned in the Introduction) to study this contrast in a wider variety of materials, including some from spontaneous conversations and extant child-centered corpora [16]. Our perceptual study is also affected by a relatively small sample size, although results are quite clear in that they suggest the contrast is easily recovered by listeners.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that most of these studies come from children in North America where young children are typically cared for by adult caregivers; much less is known about the characteristics of CDS from children in contexts in which it is common for infants to be cared for by older siblings (Brown, 2011;Zukow-Goldring, 2002). Importantly, differences in the distribution of input between adults versus older children has been shown to differ cross-culturally (Bunce et al, 2024;Scaff, Casillas, Stieglitz, & Cristia, 2024). For example, one comparative study of French-learning toddlers in France and Sesotho-learning toddlers from Lesotho in South Africa showed that the children in France heard the most input from mothers while the children in South Africa heard more of their input from other children (Loukatou et al, 2022).…”
Section: Language Input Varies By the Type Of Speakermentioning
confidence: 99%